Poor Nutrition Amidst Plenty - Mills, Dora (Maine Policy Review, 2011)
Hunger and food insecurity is on the rise in Maine as are increases in obesity, heart disease, and diabetes, all linked to food choices. Old and young, immigrant and native, rural and urban—Mainers are experiencing a food emergency made graver by the economic recession and rising health costs. Dora Anne Mills writes about “poor nutrition amidst plenty,” its causes, consequences, and the programs and policies that address it
Keywords: Maine; poor nutrition; food policy; food assistance programs